2015
DOI: 10.1185/03007995.2014.991818
|View full text |Cite
|
Sign up to set email alerts
|

Rapid resolution of sleep disturbances related to frequent reflux: effect of esomeprazole 20 mg in two randomized, double-blind, controlled trials

Abstract: Esomeprazole 20 mg significantly and effectively reduced nighttime heartburn and GERD-related sleep disturbances in the first 2 weeks of treatment compared to placebo, with rapid resolution of sleep disturbances in the first days of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Sleep quality according to the PSQI, work productivity, and regular daily activities were improved significantly in the esomeprazole group compared with the placebo group . In addition, the authors performed a similar study in which esomeprazole 20 mg for 2 weeks effectively reduced nighttime heartburn and GERD‐related sleep disturbances during the first 2 weeks of treatment . They showed that a relatively short duration of PPI treatment also improved nighttime heartburn and GERD‐related sleep disturbances.…”
Section: Role Of Nocturnal Reflux Symptoms In Sleep Disordersmentioning
confidence: 95%
See 1 more Smart Citation
“…Sleep quality according to the PSQI, work productivity, and regular daily activities were improved significantly in the esomeprazole group compared with the placebo group . In addition, the authors performed a similar study in which esomeprazole 20 mg for 2 weeks effectively reduced nighttime heartburn and GERD‐related sleep disturbances during the first 2 weeks of treatment . They showed that a relatively short duration of PPI treatment also improved nighttime heartburn and GERD‐related sleep disturbances.…”
Section: Role Of Nocturnal Reflux Symptoms In Sleep Disordersmentioning
confidence: 95%
“…57 In addition, the authors performed a similar study in which esomeprazole 20 mg for 2 weeks effectively reduced nighttime heartburn and GERD-related sleep disturbances during the first 2 weeks of treatment. 58 They showed that a relatively short duration of PPI treatment also improved nighttime heartburn and GERD-related sleep disturbances. Dexlansoprazole 30 mg once daily (n = 152) was also effective in those patients and was significantly better than placebo (n = 153) for improving GERD-related sleep disturbances (70% vs. 48%; P < 0.001).…”
Section: Effect Of Reflux Treatment On Sleepmentioning
confidence: 99%
“…Other studies have also demonstrated improvements in sleep quality following effective treatment for reflux symptoms [ 18 , 19 ]. Previous analysis of the current dataset has demonstrated that esomeprazole was associated with rapid resolution and relief of sleep disturbance and improvement in sleep quality that was significantly superior to that seen with placebo; improvements were seen as early as the first night of treatment [ 20 ]. The predictive nature of esomeprazole treatment with regard to resolution and relief of sleep disturbance after 14 days was, therefore, to be expected.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies conducted with individuals not specifically experiencing nocturnal heartburn, 43–46% of those treated with esomeprazole 20 mg were heartburn free on the first night of treatment [171]. A more detailed description of these study results is provided in Data Summaries (Online Resource 4) [176, 177]. …”
Section: Delphi Statementsmentioning
confidence: 99%